Gambaran Self Efficacay pada Penderita Diabetes Mellitus Tipe 2 di Wilayah Kerja Puskesmas Banyuanyar - Khusnul Khotimah; Ika Silvitasari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Diabetes Mellitus sufferers continue to increase. The percentage of patients with type 2 DM in Surakarta city is 24%, this figure exceeds the national target of 20%, with the number of patients in Surakarta as many as 18,833 cases, in Banyuanyar Health Center as many as 2,404. Type 2 DM disease that is not properly managed will lead to complications. Efforts that can be made to prevent these complications by increasing self efficacy in its management.Objective; Knowing the description of self efficacy in patients with type 2 diabetes mellitus. Method; The type of research used is descriptive research, with a total of 86 respondents using purposive sampling technique. The research instrument used the Diabetes Management Self Efficacy Scale (DMSES).Results; From the results of the study, the majority of respondents' characteristics were based on age 40-64 years (74.4%), female gender (65.1%), high school education level (37.2%), self-employed work (43.0%), long suffering from DM ≥5 years (57.0%) and sufficient self efficacy category (41.9%). Conclusion; Self efficacy of patients with Type 2 Diabetes Mellitus in the Banyuanyar Health Center working area is in the moderate category